1978
DOI: 10.3189/s0022143000198041
|View full text |Cite
|
Sign up to set email alerts
|

Some Measurements of Settlement in a Rocky Mountains Snow Cover

Abstract: ABSTRACT. Snow-cover settlement was measured in a dry, annual sub-alpine snow cover in the Colorado Rockies with settlement gages. Settlement viscosities were calculated from the change in gage heights over various periods during the winter and early spring, and the associated overburden over the gages as estimated from density measurements and precipitation records. When adjustments are made for local snow temperature, viscosities are in fair agreement with values found in the literature from similar snow cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…All of these processes can be treated together by making the assumption that the snow behaves as a viscous fluid with an “effective” compactive viscosity, η c (Keeler, 1967; Kojima, 1967; Bergen, 1978; Qin Dahe, 1990): where h is the thickness of the layer, t is time, ρ is density and σ is the load. Values of η c have been determined from observations of the settlement of natural snow layers, from uniaxial-strain compressive tests and from depth-density profiles on glaciers and ice sheets.…”
Section: Calculating Time-density Curves Using a Viscous Modelmentioning
confidence: 99%
“…All of these processes can be treated together by making the assumption that the snow behaves as a viscous fluid with an “effective” compactive viscosity, η c (Keeler, 1967; Kojima, 1967; Bergen, 1978; Qin Dahe, 1990): where h is the thickness of the layer, t is time, ρ is density and σ is the load. Values of η c have been determined from observations of the settlement of natural snow layers, from uniaxial-strain compressive tests and from depth-density profiles on glaciers and ice sheets.…”
Section: Calculating Time-density Curves Using a Viscous Modelmentioning
confidence: 99%
“…It was concluded that under these conditions natural densification of a snow cover is determined primarily by the load, and not by metamorphism of the snow grains. Bergen (1978) noted that in a dry, annual snow-cover settlement is a strong function of rate ofloading, thermal regime, and sample density. While this study primarily involved fine-grained snow (grain sizes in the vicinity of 1.0 mm) the author did note an apparent tendency for viscosity to increase with grain-size.…”
Section: Introductionmentioning
confidence: 99%
“…Viscosity can be calculated from compaction rate and expressed in terms of congealation of snow grain crystals (Keeler, 1967;Kojima, 1974;Bergen, 1978;Sturm and Holmgren, 1998) as:…”
Section: Compaction Parameters Of Fresh Snowmentioning
confidence: 99%